Main sources of subsidy in Agriculture - Eduard Alexandru Dumitru; Dalila Stoica (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Agriculture is a risky and often expensive activity, where due to unpredictable weather conditions, crops may suffer and implicitly farm yields and incomes that may be significantly affected. The paper presents the main sources of subsidies used in agriculture, as well as the role they played in changing areas, production and selling prices of agricultural products. Direct payments through: single area payment scheme, redistributive payment, payment for young farmers, scheme for small farmers, greening payment, coupled support and Transitional National Aid contributed to farm support. The data used in this study come from APIA, and for their analysis the methods of quantitative and qualitative data analysis were used.
Keywords: Q14; Q18; 330; financing; agriculture; sources of financing; direct payments; transitional national aid